Vessel [compact disc] (Fueled By Ramen, LLC, 2012)
Twenty One Pilots fuses elements of hip-hop, indie rock and punk to create a unique sound to support their uplifting lyrical messages. Includes the songs Ode to Sleep, Migraine, and Car Radio.